Identitas Politik dan Multikulturalisme: Penguatan Identitas Politik Etnis Tionghoa Pasca Orde Baru - Suryani Suryani; Ana Sabhana Azmy (PERSPEKTIF, 2020)
Reformation movement of 1998 being a starting point from so many dynamical changing of national politics in Indonesia. Chinese that has a strong historical root in Indonesia, being one of part of societies that used the reformation momentum as a way to involve into politics. This article analyzed the phenomena of strengthening Chines political identity post new order, and to analyzed the relation between strengthening Chinese political identity and multiculturalism in Indonesia.By using a qualitative methodolgy, those collected datas in this research, was analyzed by political identity theory, multiculturaism concept, and social capital theory. This research found that there are things that relate to the strengthening Chinese political identity post new order in Indonesia. The changing of political orientation of Chinese occured because the strong social capital and the changing of government policy that relate to the citizenship status. Those supported by a good understanding of multiculturalism by Indonesian society.